Erasmus and his books - Gulik, Egbertus van, 1910-1998 (Erasmus studies., 2018)
"Part 1 tells the story of the formation, growth, scope, and disposal of Erasmus' library with an analysis of his relationship in his books. Part 2 is an annotated catalogue of all the items known to have been contained in Erasmus' library."--